2015
DOI: 10.14474/ptrs.2015.4.2.73
|View full text |Cite
|
Sign up to set email alerts
|

Effects of body weight-supported treadmill training combined with ball-kicking on balance and gait of subacute stroke patients

Abstract: Objective: This study focused on subacute stroke patients who were asked to kick a ball while walking on a treadmill. The aim of the study was to determine the effect of a body weight-supported treadmill training (BWSTT) combined with ball-kicking on muscle strength, balance, and gait. Design: Single blind, randomized controlled trial. Methods: Twenty stroke patients who volunteered to participate in this study were randomly assigned to either the BWSTT combined with ball-kicking (BWSTT-BK; 10 participants) gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…As a result, subjects with POMA gait scale scores of >8.5 were excellent at functional ability (the OLST of affected side, SST, FM-LE, and TIS) compared with subjects with POMA gait scale scores ≤8.5. In general, stroke patients have impaired postural stability [32] and thus rely more heavily on the lower extremity of the non-affected side to maintain balance, and the asymmetrical weight bearing becomes severe [33,34]. In addition, as stroke patients rely more heavily on vision than proprioceptor when performing the OLST [35], postural sway appears more significant and it also has a negative impact on postural control.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, subjects with POMA gait scale scores of >8.5 were excellent at functional ability (the OLST of affected side, SST, FM-LE, and TIS) compared with subjects with POMA gait scale scores ≤8.5. In general, stroke patients have impaired postural stability [32] and thus rely more heavily on the lower extremity of the non-affected side to maintain balance, and the asymmetrical weight bearing becomes severe [33,34]. In addition, as stroke patients rely more heavily on vision than proprioceptor when performing the OLST [35], postural sway appears more significant and it also has a negative impact on postural control.…”
Section: Discussionmentioning
confidence: 99%
“…For persons with stroke who have movement and cognitive impairments, it is necessary for them to walk and exercise or perform a cognitive task simultaneously for the prevention of falls during the performance of daily life activities [7]. Choi et al [16] reported improved dynamic balance abilities in dual-task training treadmill training group that followed audible instructions to transfer rings compared to the TGT group.…”
Section: Discussionmentioning
confidence: 99%
“…Persons who had been diagnosed with stroke at least 6 months ago, thus indicating a chronic stroke, persons who were able to follow instructions and with an Mini-Mental State Examination score of greater than 24 [7], and those who were able to ambulate at least 10 m independently with or without an assistive device were selected to participate in the study [15]. Persons with a heart or orthopedic disorder and those with visual or auditory problems were excluded from this study [15].…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations